Rust Infection of Black Poplar Trees Reduces Photosynthesis but Does Not Affect Isoprene Biosynthesis or Emission - Eberl, Franziska; Perreca, Erica; Vogel, Heiko; Wright, Louwrance P.; Hammerbacher, Almuth; Veit, Daniel; Gershenzon, Jonathan; Unsicker, Sybille B. (Frontiers in Plant Science, 2018)
Poplar (Populus spp.) trees are widely distributed and play an important role in ecological communities and in forestry. Moreover, by releasing high amounts of isoprene, these trees impact global atmospheric chemistry. One of the most devastating diseases for poplar is leaf rust, caused by fungi of the genus Melampsora. Despite the wide distribution of these biotrophic pathogens, very little is known about their effects on isoprene biosynthesis and emission. We therefore infected black poplar (P. nigra) trees with the rust fungus M. larici-populina and monitored isoprene emission and other physiological parameters over the course of infection to determine the underlying mechanisms. We found an immediate and persistent decrease in photosynthesis during infection, presumably caused by decreased stomatal conductance mediated by increased ABA levels. At the same time, isoprene emission remained stable during the time course of infection, consistent with the stability of its biosynthesis. There was no detectable change in the levels of intermediates or gene transcripts of the methylerythritol 4-phosphate (MEP) pathway in infected compared to control leaves. Rust infection thus does not affect isoprene emission, but may still influence the atmosphere via decreased fixation of CO2.